2015
DOI: 10.1007/s11440-015-0421-9
|View full text |Cite
|
Sign up to set email alerts
|

Formation and development of salt crusts on soil surfaces

Abstract: The salt concentration gradually increases at the soil free surface when the evaporation rate exceeds the diffusive counter transport. Eventually, salt precipitates and crystals form a porous sodium chloride crust with a porosity of 0.43 ± 0.14. After detaching from soils, the salt crust still experiences water condensation and salt deliquescence at the bottom, brine transport across the crust driven by the humidity gradient, and continued air-side precipitation. This transport mechanism allows salt crust migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 31 publications
2
47
0
Order By: Relevance
“…The microscopic images reveal that the salt crust formed at the surface of the porous media is itself porous and evolves in a highly dynamic way due to the complex interplay of crystallization and evaporation at the crystal-liquid, crystal-crystal, liquidair, and the crystal-air interfaces [Shahidzadeh et al, 2015]. This is in agreement with the results reported recently by Dai et al [2016] showing that NaCl "preferentially precipitates in cubic-shaped crystals that are packed heterogeneously to form a very porous structure." The recorded images also indicate that formation of salt does not necessarily clog the pores; the continued growth of salt crystals above the precipitated salt indicates further water evaporation with vaporization occurring at the salt surface.…”
Section: Effects Of the Precipitated Salt At The Surface On The Evaposupporting
confidence: 89%
See 2 more Smart Citations
“…The microscopic images reveal that the salt crust formed at the surface of the porous media is itself porous and evolves in a highly dynamic way due to the complex interplay of crystallization and evaporation at the crystal-liquid, crystal-crystal, liquidair, and the crystal-air interfaces [Shahidzadeh et al, 2015]. This is in agreement with the results reported recently by Dai et al [2016] showing that NaCl "preferentially precipitates in cubic-shaped crystals that are packed heterogeneously to form a very porous structure." The recorded images also indicate that formation of salt does not necessarily clog the pores; the continued growth of salt crystals above the precipitated salt indicates further water evaporation with vaporization occurring at the salt surface.…”
Section: Effects Of the Precipitated Salt At The Surface On The Evaposupporting
confidence: 89%
“…This is in agreement with the results reported recently by Dai et al . [] showing that NaCl “preferentially precipitates in cubic‐shaped crystals that are packed heterogeneously to form a very porous structure.” The recorded images also indicate that formation of salt does not necessarily clog the pores; the continued growth of salt crystals above the precipitated salt indicates further water evaporation with vaporization occurring at the salt surface. Microscopic analysis suggests that the presence of porous salt at the surface causes top‐supplied creeping of the solution, feeding the growth of subsequent crystals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Figure 3 it is clearly seen that ESC formation is a dynamic process where the crust is continually evolving and the morphological changes of the ESC could be a result of (1) dissolution processes that take place at the lower boundary of the ESC as the ESC continuously experiences water condensation and salt deliquescence at its bottom boundary and precipitation of new crystals at its upper boundary (Dai et al, 2016) and (2) mechanical pressure that is being applied by the growing salt crystals. It is well known that a growing salt crystal exerts pressure on solids that are in contact with it (Espinosa et al, 2008;Rodriguez-Navarro & Doehne, 1999;Zehnder & Arnold, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al (2016) showed that a NaCl crust tends to create domes over the surface of the evaporating porous medium; thus, there is no direct contact between the evaporating matrix and the salt crust. Dai et al (2016) showed that a NaCl crust tends to create domes over the surface of the evaporating porous medium; thus, there is no direct contact between the evaporating matrix and the salt crust.…”
Section: Introductionmentioning
confidence: 99%